Static- vs. Dynamic-Stretching in Development of the Dynamic Balance; Chronic Effects of Specific Training Interventions in Female Football Players - Mijatovic, D.; Pehar, M.; Versic, S.; Kvesic, I.; Gabrilo, G. (SportMont, 2023)
Flexibility is an important determinant of dynamic balance, but studies rarely examined the chronic effects of flexibility training on changes in balance capacity. This study aimed to determine the influence of different forms of flexibility exercises on dynamic balance in female professional football players. Participants were 30 female professional football players (age =19.0±4.1 years), divided into three groups dynamic stretching group (DSG; N=10, age =18.9±3.3 years), static stretching group (SSG; N=10, age =19.5±4.3 years) and control group (N=10, age =18.5±3.3 years). All groups participated in equal football training, while DSG and SSG performed additional flexibility training 3-times a week (10-15 min of duration) throughout the study course (16 weeks). Dynamic balance was measured by the Y-balance test (YBT), and ANOVA for repeated measurement was applied to identify the effects. Results evidenced the significant influence of both flexibility programs on dynamic balance. Both DSG and SSG were equally effective in the first part of the study (until the 8th week), but between the 8th and 16th study week, only DSG improved their balance capacity significantly. Static stretching should be applied in the first phases of flexibility training aiming at the improvement of dynamic balance, but in later phases, usage of dynamic stretching is suggested.